A pilot study of the primary care management of knee osteoarthritis in the Northern States of Malaysia - A, Arshad; R, Rashid (IIUM Medical Journal Malaysia, 2008)
Introduction: Primary care management of knee osteoarthritis OA has received little attention in the scientific literature and the main reason of this survey is to study and explore the variations and patterns of primary care management and assess both conventional and complementary therapy usage in knee OA in the primary care setting. Materials and Methods: A cross sectional survey of 100 randomly selected general practitioners (GPs) in the northern states of Malaysia (Kedah, Perlis, Pulau Pinang) was undertaken using questionnaires. The GPs involved were asked about basic knowledge of OA in terms of diagnosis, investigation, and treatment of OA. They were also asked their usage of conventional and complementary medication. Results: 80 (80%) GPs responded to the questionnaires sent. 85% of GPs were in solo practice and 15% in group practice. Most of the GPs surveyed (69%) were in practice for more than 10 years, 21% in 5- 10 years and 10% were in practice for less than 5 years. 65% GPs surveyed see an average of more than 20 patients per week, 25% see about 10- 20 patients and 10% see less than 10 patients per week. 75% of GPs surveyed would arrange an X-ray. 65% of GPs surveyed will arrange a blood test, mostly serum uric acid, rheumatoid factor and ESR. Pharmacological management consists of first line treatment with analgesics (32%), NSAIDs (59%) or a combination of the two (4%). Non-pharmacological management consist of advise an exercise (37%), weight reduction (23%) and referral to physiotherapy (8%). 89% of GPs surveyed prescribed some form of complementary medications. 68% prescribed glucosamine sulphate, 29% chondroitin sulphate, 18% cod liver oil, 12% evening primrose oil. Only 5% of GPs surveyed perform intra- articular injection. Conclusion: The data suggest that in the primary care, majority of GP over investigate the diagnosis of OA. Pharmacological interventions largely concentrate on analgesic and NSAIDs. The use of physiotherapy and non drug approach were enormously under-utilized. There is a need to further educate GPs in the management of OA.